Comparative Study on the Construction Time of Spun Pile and Bored Pile Foundations in Cohesive Soil: A Case Study of the Aqueduct X Project - Helmi Aziz, Ghufran; Patriadi, Andi; Wulandari, Esti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The selection of foundation type plays a crucial role in ensuring the safety, efficiency, and cost-effectiveness of civil infrastructure, particularly for projects constructed on cohesive soils. This study presents a comparative analysis of the implementation time between bored pile and spun pile foundation works on the Aqueduct X structure located in Aceh Province, Indonesia. The research was carried out based on soil data obtained from borehole investigations and analyzed using the bearing capacity method for cohesive soils following Skempton (1966) in Yelvi et al. (2023). The total required foundation length for all aqueduct structures was determined to be 22,592 meters. The production capacity of bored pile works was calculated at 7.66 m/hour, while that of spun pile works was 8.71 m/hour. Using an 8-hour working day as a reference, the total duration for bored pile installation was estimated at 360 calendar days, compared to 325 calendar days for spun pile installation. The results indicate that the spun pile method provides a time efficiency advantage of approximately 35 days compared to the bored pile method. However, to comprehensively assess the overall effectiveness, further analyses—including cost and quality comparisons—are recommended. This research contributes to the optimization of foundation selection and construction planning in cohesive soil conditions, supporting efficient decision-making for future infrastructure development.